ON ISSUES OF EVIDENCE EVALUATION IN CRIMINAL PROCEEDINGS UNDER MARTIAL STATE (Bulletin of criminological association of Ukraine, 2025)
The scientific article examines the features of evidence assessment in criminal proceedings under the legal regime of martial law. The emphasis is on the fact that evidence assessment is a separate element of the evidence process, and therefore a type of specific activity of authorized participants in criminal proceedings. Approaches that directly relate to the assessment of evidence in different historical periods are studied, and the experience and criteria for assessing evidence in some countries of the world community are also used. The issue of defining the concept of "internal conviction" during the assessment of evidence by an investigator, inquirer, prosecutor, investigating judge, and court in criminal proceedings is considered. Given the above, we believe that the main disadvantage of internal conviction is the influence of subjective and objective factors on making relevant decisions in criminal proceedings. The author's vision is set out on improving the procedure for assessing evidence, which is an important factor for identifying occupiers involved in committing criminal offenses and further fair justice.
Keywords: criminal process; elements of the evidentiary process; evidence; evidence assessment; internal conviction; legal regime of martial law